Gamification in for-profit organisations: A mapping study - László Szendrői; Krishna S. Dhir; Katalin Czakó (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This study reviews prevailing trends in 'for-profit' business-related gamification. It examines the current literature, focusing on gamification elements, industries and variables that is of interest to researchers in different business environments. A systematic mapping approach was applied to this study. Articles were selected from different databases in a two-step screening process, subject to sets of inclusion and exclusion criteria. A total of 25 articles were further for: (1) represented industries, (2) orientation of the gamified system, (3) types of implementation, (4) gamification elements analysed, (5) impact on companies, and (6) company variables analysed. Results confirmed that the number of empirical studies on gamification in for-profit organisations is growing. Researchers have placed greater emphasis on analysing customer-related gamification environments than on employee-oriented gamification. This finding is consistent with the prevailing trend of increasing demand from practitioners to gamify customer-related processes. This is likely due to the potential for higher positive impact on the performance of companies. Most frequently deployed gamification elements are badges, rewards, and leader boards. The literature suggests that over all, gamification has a positive effect on various company variables, such as motivation, engagement of employees, brand loyalty, and customer experience. This paper highlights the particular areas of business-related gamification that have already been examined and possible future directions.
Keywords: M00; 650; gamification; organisations; customer environment; engagement; motivation; mapping study; badges; levels; points